Indigenous economics : sustaining peoples and their lands - Trosper, Ronald L. (The University of Arizona Press, 2022)
"The book explains how Indigenous peoples organize their economies for good living, by developing relationships among people and the natural world. Creating strong relationships is a major alternative to the proposals that urge Indigenous people to individualize their economies"--